Effect of Thermal-Mechanical Coupling on Gas Permeability Properties and Pore Structure of HTCC - ZHANG Deng-xiang, ZENG Zhe, JIANG Zhong-ming (长江科学院院报)
[Objectives] Traditional concrete is prone to brittle cracking under complex thermal-mechanical coupling conditions, which significantly increases the risk of gas leakage from underground gas storage reservoirs in Compressed Air Energy Storage (CAES) power stations. High-toughness cementitious composites (HTCC), due to their excellent toughness and impermeability, are considered as a potential structural lining material for CAES underground gas reservoirs. This study systematically investigates the gas permeability property and the evolution mechanism of the micro-pore structure of HTCC under thermal-mechanical coupling from an experimental perspective. A quantitative relationship between operational parameters (e.g., temperature and pressure) and gas permeability property is established, providing references for material selection in energy storage infrastructure. [Methods] Five groups of HTCC test specimens with different mix proportions were prepared. Their basic mechanical properties were evaluated through uniaxial tensile tests, and the mix with the best mechanical performance was selected to prepare ten groups of test specimens. Based on typical CAES operational conditions, nine test schemes were designed under a pressure of 10 MPa and temperature of 150 ℃. A self-developed temperature and pressure synchronized cyclic loading tester was used to simulate these operational conditions, and the ten groups of HTCC test specimens were subjected to ten cycles of loading. After the cycles, high-pressure gas permeability tests and mercury intrusion porosimetry tests were conducted to evaluate the effects of thermal-mechanical coupling on the gas permeability property and pore structure of HTCC. [Results] (1) The tensile-compressive strength ratio of HTCC reached 0.16, with a peak tensile strain exceeding 0.7% and an average crack width between 41-49 μm. HTCC demonstrated excellent tensile toughness and crack control capability, making it highly suitable for use in concrete lining structures of CAES reservoirs, and with optimized mix design, may also be applicable to the sealing layer. (2) The average gas permeability of the HTCC control group was 4.09×10-18 m2, and significant increases in permeability were observed after temperature and pressure synchronized cyclic loading. Under three pressure combinations (0-5 MPa, 0-7.5 MPa, and 0-10 MPa), when temperature increased from 25-50 ℃ to 25-150 ℃, three groups of test specimens showed maximum gas permeability increases of 112.7%, 183.6%, and 508.8%, respectively, compared to the control group. Moreover, temperature and pressure had distinct effects on permeability, with permeability being more sensitive to pressure than to temperature. (3) The gas permeability gradually decreased with increasing inlet pressure but tended to stabilize when the inlet pressure exceeded 3 MPa. (4) When the reservoir pressure was within 0-7.5 MPa, and the internal temperature reached 100 ℃, although the pore structure of HTCC changed, the critical pore diameter remained stable, and the permeability stayed within the order of 10-18 m2, which generally met the impermeability requirements of CAES reservoirs. However, when the operating pressure reached 10 MPa, the critical pore diameter increased, pore coarsening occurred, and new cracks formed, resulting in rapid degradation of impermeability. Therefore, if HTCC was to be used as the lining or sealing layer under 10 MPa pressure, it was recommended that its design compressive strength should exceed 40 MPa. [Conclusions] With excellent tensile toughness and crack control capability, HTCC can be applied to concrete lining structures of underground gas reservoirs in CAES power stations. When the operating pressure reaches 10 MPa, the impermeability of HTCC deteriorates rapidly. If HTCC is used as the sealing layer, its mix design should be optimized accordingly.